Violence Against Women: Reflecting on 25 Years of the Violence Against Women Act and Directions for the Future - Moore, Angela M. (Violence against women, 2021)
The year 2019 marked the 25th anniversary of the passage of the landmark legislation, the 1994 Violence Against Women Act (VAWA). As we reflect on the Act, it is important to examine how the VAWA influenced the response to violence against women. This guest editors’ introduction provides a preview of five articles devoted to a special issue of Violence Against Women. The articles highlight key aspects of VAWA. With H.R. 15851 awaiting consideration by the Senate, we suggest that perhaps now is an appropriate time to assess the Act’s impact.